Variables Influencing Susceptibility Testing of Cryptococcus neoformans to 5-Fluorocytosine - Block, Edward R. (1973)
The minimum inhibitory concentration (MIC) of 5-fluorocytosine (5-FC) was determined for 65 isolates of Cryptococcus neoformans by using a twofold serial tube dilution method. The MIC was profoundly influenced by incubation temperature, inoculum size, and duration of incubation. By using a standard set of test conditions, 100% of 49 pretreatment isolates of C. neoformans were susceptible to 10 μg of 5-FC per ml or less, and 9 (56%) of 16 isolates recovered during or after 5-FC therapy were massively drug resistant (MIC > 320 μg/ml). With the standard test conditions recommended here, the tube dilution method was found to be both accurate and reproducible, and the results correlated with the treatment status of patients.